The influence of direct-to-physician promotion towards physicians’ prescription in behaviour in Malaysia - Sardar, Md Humayun Kabir; Maulan, Suharni; Abd. Manaf, Noor Hazilah; Wan Nasir, Zaireena (Emerald Publishing, 2022)
Purpose – The purpose of this paper is to investigate the influence of direct-to-physician promotion on physicians’ prescription behaviour. There were very few studies which have investigated to what extent the pharmaceutical promotion directed towards physicians influences physicians’ prescription behaviour in the Malaysian context. Design/methodology/approach – A research framework has been developed based on the buyer behaviour stimulus-response model. A survey method has been used to collect data from 154 medical practitioners from private health-care facilities located at Klang valley in Malaysia. IBM SPSS and SmartPLS statistical programs have been used to analyse the data and validate the model. Findings – This study found that personal selling is the most significant promotional tool for physicians’ prescription behaviour, whereas advertising is the least significant one. Sales promotion and public relations are the second and third most significant promotional tools. Direct marketing is found to be not significant. Practical implications – This paper will help the pharmaceutical companies develop more effective plans to gain a competitive advantage for their business by having a guideline for pharmaceutical marketers as an input to the more efficient allocation of their promotional budgets. Originality/value – This study has introduced a comprehensive understanding of all the factors in the pharmaceutical promotion that influence physicians’ prescription behaviour in Malaysia and how these factors are interrelated, influencing physicians’ prescribing medicines for patients.